2017
DOI: 10.1073/pnas.1613445114
|View full text |Cite
|
Sign up to set email alerts
|

Imaging individual neurons in the retinal ganglion cell layer of the living eye

Abstract: Although imaging of the living retina with adaptive optics scanning light ophthalmoscopy (AOSLO) provides microscopic access to individual cells, such as photoreceptors, retinal pigment epithelial cells, and blood cells in the retinal vasculature, other important cell classes, such as retinal ganglion cells, have proven much more challenging to image. The near transparency of inner retinal cells is advantageous for vision, as light must pass through them to reach the photoreceptors, but it has prevented them f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
158
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(166 citation statements)
references
References 51 publications
6
158
0
2
Order By: Relevance
“…This would offer the possibility to adjust the compromise between contrast and SNR in postdetection. Previous research have reported the use of annular apertures for narrow field of view (<30 deg) 13,[17][18][19][21][22][23] or the combination of information from differently shaped apertures for very narrow field of view (<1 deg); 20,23,24 our multimode implementation provides a wide-field capability (the native field of view of the SLO, of up to 200 deg) and high-contrast imaging simultaneously.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This would offer the possibility to adjust the compromise between contrast and SNR in postdetection. Previous research have reported the use of annular apertures for narrow field of view (<30 deg) 13,[17][18][19][21][22][23] or the combination of information from differently shaped apertures for very narrow field of view (<1 deg); 20,23,24 our multimode implementation provides a wide-field capability (the native field of view of the SLO, of up to 200 deg) and high-contrast imaging simultaneously.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, an annular aperture offers the complementary function of recording only the scattered light, rejecting the direct backreflection contribution; this mode of operation is called indirect, scatter, dark-field, or Tyndall-mode. 8,10,11,13,[17][18][19][20] Several researchers have reported on the benefit provided by the use of different pinhole apertures as spatial filters, 13,[17][18][19][21][22][23] including multichannel imaging, 20,23,24 however, confocal imaging with small pinholes is limited to relatively small fields of view of <30 deg or an order-of-magnitude less than this for diffraction-limited imaging achievable with adaptive-optics correction. [25][26][27][28] The effect of optical aberrations on the image of the retina is much more severe than for the illuminating beam since image formation uses the whole pupil, so the numerical aperture for the imaging return path is typically 10 times greater than for the illuminating beam yielding commensurately higher levels of aberration.…”
Section: Introductionmentioning
confidence: 99%
“…The presented work leverages the split-nature of the appearance of the photoreceptors in AOSLO non-confocal images, and creates a model of the photoreceptors that is subsequently used by a classification framework. Naturally, if a different split detection of offset pinhole is used, as in [13], the algorithm would need adjustments and adaptations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…More recently, groups began to investigate non-confocal imaging [12,13]. The work in [12] used a non-confocal split-detection technique to image the photoreceptor's inner segments, and improved identification of photoreceptors in retinal dystrophies [see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mais l'imagerie des cellules ganglionnaires, quasiment transparentes et peu contrastées, n'a été possible que grâce à une astuce elle aussi issue de la microscopie : en décalant lé-gèrement le trou confocal de réception de la position de la source ponctuelle, Figure 3. Haut : schéma du brevet de M Minsky pour l'ophtalmoscope confocal [5] ; bas : trois images en champ sombre : gauche, cellules ganglionnaires [6] en multioffset detection ; centre, vaisseaux et leurs globules (image prise par K Grieve en champ sombre) ; droite, segments internes de photorécepteurs [7] en split detection. Images : 1×1° de champ.…”
Section: La Révolution Confocaleunclassified